2015
DOI: 10.1007/s00402-015-2366-8
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial evaluation of a point-of-care educational app on medical topics in orthogeriatrics

Abstract: IntroductionResearch by AOTrauma’s orthogeriatrics education taskforce identified ongoing educational needs for surgeons and trainees worldwide regarding the medical management of older adults with a fracture. To address practicing surgeons’ preference for increased use of mobile learning, a point-of-care educational app was planned by a committee of experienced faculty. The goals were to deliver the app to surgeons, trainees, and other healthcare professionals, to measure usage, and to evaluate the impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The system development of mobile health apps mainly includes a user-computer interface, algorithms, privacy, design, and computer security, and it follows the principles of user-centered, convenient operation, safety, and stability [ 22 , 23 ]. As a new product, the effectiveness, quality, and accuracy of various mobile health apps used in health care need to be continuously evaluated through academic research [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The system development of mobile health apps mainly includes a user-computer interface, algorithms, privacy, design, and computer security, and it follows the principles of user-centered, convenient operation, safety, and stability [ 22 , 23 ]. As a new product, the effectiveness, quality, and accuracy of various mobile health apps used in health care need to be continuously evaluated through academic research [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…mHealth approaches are transversal to a wide set of application domains such as cardiac [ 31 ], trauma [ 32 ] and pain assessment [ 33 ], obesity and diabetes [ 34 ], mental health [ 35 , 36 ], medication adherence [ 37 ], and chronic diseases [ 38 ] and target: (a) healthcare professionals and care givers (e.g., [ 39 ]), to support patient assessment and monitoring; (b) patients, from all ages [ 40 ], for self-management, and as providers of relevant information for their condition; and (c) for the training of students and professionals, in certain domains (e.g., [ 41 ]), and as a way to bring caregivers onboard, by having them adopt guidelines and practises [ 42 , 43 ].…”
Section: Mobile Health and Geriatric Patient Assessmentmentioning
confidence: 99%
“…To the best of our knowledge, one important aspect that is also missing in existing applications concerns the formative aspects, an important part of our goals, and recognized as an important requirement to move CGA forward in geriatric care [ 54 ]. In fact, this kind of approach has already been considered in other areas [ 41 , 42 , 43 , 55 ] with success. However, it is important to note that care should be taken since providing the clinicians with something that only partially supports CGA might, at some point, be taken as defining what a CGA actually is [ 14 ], which might limit its potential.…”
Section: Mobile Health and Geriatric Patient Assessmentmentioning
confidence: 99%
“…This latter phase, in addition to improvement through gaining experience, might be further deepened by conveying the use of CGA tools including apps to assess multidimensional prognosis and thereby improving clinical decision making in older patients. [32][33][34][35] Indeed, it has been recently shown that targeted educational events using operatively aligned outcome-centered learning objectives improves the effects of geriatric multidimensional interventions on patient overall outcomes as assessed by the multidimensional prognostic index (MPI). In these preliminary observations, [36][37][38] a team specifically trained based upon constructive alignment of theoretic learning objectives with practical learning outcomes, produces more significant improvements in the CGAbased MPI -already shown to accurately measure overall in-hospital disease/recovery course 39 -from admission to discharge with respect to standard of care.…”
Section: Comprehensive Geriatric Assessment Education and Trainingmentioning
confidence: 99%